Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Hotel Grandhika Setiabudi Medan - Purnama Romianta Tarulina Sinaga; Agus Mariani Saragih; Erwinsyah Simanungkalit; Jumjuma Jumjuma; Nursiah Nursiah (Universitas 45 Surabaya, 2024)
Hotel business is one of the service businesses that sells various forms of accommodation, which include elements of comfort, service, and various facilities designed for customers who require lodging facilities for both work and leisure purposes. Currently, the competition in the hotel industry is becoming increasingly fierce, making it crucial for every company to recognize the importance of customer loyalty to ensure the sustainability of their business. The quality of service provided by the company is a crucial factor in creating satisfaction for each hotel customer. This study aims to investigate how the influence of service quality, both partially and simultaneously, affects hotel customer satisfaction. The population in this study consists of Hotel Grandhika Medan guests who incidentally stayed at Hotel Grandhika Setiabudi Medan, with a sample size of 80 people selected using accidental sampling. This study is a quantitative research with data collection techniques conducted through questionnaires and literature reviews. The data analysis method in this study includes validity tests, reliability tests, class assumption tests, simple linear regression, and hypothesis tests. From the results of this study, it was found that 62.8% of customer satisfaction is explained by the service quality variable, while 37.2% is influenced by other variables not studied in this research. The results of this study show that the service quality variable has a positive and significant partial effect on hotel customer satisfaction at Hotel Grandhika Setia Budi Medan, particularly influenced by the hotel's consistent polite behavior towards customers.